Effects of Explosion Shock Waves on Lung Injuries in Rabbits. (10th February 2021) - Sun, Yanlong; Qian, Xinming; Shu, Chi-Min; Li, Ziyuan; Yuan, Mengqi; Zhang, Qi; Li, Yanteng
Abstract : The purpose of this study was to explore the damage effects and injury mechanism of free-field explosion shock waves on rabbit lungs. Six free-field explosion experiments, each with 500 g trinitrotoluene (TNT), were conducted as the shock wave overpressure acting on the rabbits was measured. The peak overpressure of the shock wave was 533, 390, 249, 102, and 69 kPa at the respective test points. Damage to the rabbit lungs caused by shock wave overpressure was investigated through observation, anatomical analysis, and hematoxylin-eosin (HE) staining processing. The shock wave overpressure of 69–102 kPa caused mild-to-moderate injury; the shock wave overpressure of 102–249 kPa caused moderate injury; the shock wave overpressure of 249–390 kPa resulted in moderate-to-severe injury; and the shock wave overpressure of 390–533 kPa caused severe injury to the rabbit. Mild, moderate, and severe injuries destroyed some, most, or all alveolar structures, correspondingly, as well as producing partial cell apoptosis. The overpressure damage mechanism primarily involves the collapse and rupture of pulmonary alveolus in the lung tissue. As a novel attempt, the investigation provided here may serve to improve the current shock wave injury mechanism.